PARENTAL SUPPORT AND PEER ENVIRONMENT ON ACADEMIC ACHIEVEMENT THROUGH LEARNING MOTIVATION MEDIATION - Ratumbuisang, Laura Walanda; Mardi; Zulaihati, Sri (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
The aim of this research is to examine the influence of parental support and peer environment on student academic achievement, as well as to understand the mediating role of learning motivation in this relationship. This study uses a quantitative research approach. In the data collection process, researchers distributed questionnaires to respondents. In addition, secondary data used were the grade point average (GPA) of students of the Faculty of Economics class of 2020. Proportional random sampling technique was used, with a sample size of 217 people. Data were analyzed with the help of the SPSS 27 program. Parental support and the peer environment positively influence academic achievement and learning motivation. Parental support and a supportive peer environment significantly enhance students' learning motivation, which in turn improves academic performance. Learning motivation acts as a mediator between both parental support and peer influence, and academic achievement. Thus, strong parental support and a positive peer environment are crucial for boosting students' motivation and academic success.